Adenoid cystic carcinoma of the trachea - Heena M Desai; Rohit Thakare; Gayathri P Amonkar; Vinaya Karkhanis; Jyotsna M Joshi (Wolters Kluwer Medknow Publications, 2015)
Primary salivary gland - type tumors of the lung and airways being unusual, they pose a diagnostic challenge on small biopsies and are usually consigned as non-small cell lung carcinomas. Since the clinical behavior of these tumors is different from the conventional lung tumors, it is important to accurately diagnose them. Among this category of tumors, adenoid cystic carcinoma (ACC) of the lungs and airways is exceedingly rare. Few large studies and maximum case reports have been reported in literature on ACC of the lungs and trachea so far. We herein report a rare case of primary ACC of the trachea diagnosed on bronchoscopic biopsy.